Memory reconsolidation: a proposed change mechanism for the arts therapies - Hass-Cohen, Noah; Clay, Jennifer C. (Frontiers in Cognition, 2025)
It is proposed that memory reconsolidation (MR) processes are a common therapeutic change mechanism for arts therapies and that arts therapies' processes uniquely facilitate the MR of autobiographical and distressing memories. This study aims to review memory reconsolidation, identify the necessary neuroscientific conditions for therapeutic MR, and examine the alignment between Art Therapy Relational Neuroscience (ATR-N) principles, interventions, and MR conditions. A comprehensive description of two ATR-N MR case drawing protocols is provided along with application guidelines based on two decades of research on the ATR-N drawing protocols.